1992
DOI: 10.1073/pnas.89.4.1315
|View full text |Cite
|
Sign up to set email alerts
|

Human carbonic anhydrase IV: cDNA cloning, sequence comparison, and expression in COS cell membranes.

Abstract: We have isolated a full-length cDNA for human carbonic anhydrase IV (CA IV) from a AgtlO human kidney cDNA library. The 1105-base-pair (bp) cDNA contains a 47-bp 5' untranslated region, a 936-bp open reading frame, and a 122-bp 3' untranslated region. The deduced amino acid sequence is colinear with the N-terminal sequence and the sequence of several tryptic peptides of human lung CA IN. It includes an 18-amino acid signal sequence, a 260-amino acid region that shows 30-36% similarity with the 29-kDa cytoplas-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 42 publications
2
59
0
2
Order By: Relevance
“…The issue became confused when Wolfensberger et al (12) reported a 54-kDa protein in human retina, which they called CA IV. Because human CA IV is a 35-kDa nonglycosylated protein (25), it seems likely they misidentified CA XIV as CA IV, because the former had not yet been identified. From our own studies and those of Ochrietor et al (15), it is clear that CA XIV is the major membrane-associated CA in retina.…”
Section: Discussionmentioning
confidence: 99%
“…The issue became confused when Wolfensberger et al (12) reported a 54-kDa protein in human retina, which they called CA IV. Because human CA IV is a 35-kDa nonglycosylated protein (25), it seems likely they misidentified CA XIV as CA IV, because the former had not yet been identified. From our own studies and those of Ochrietor et al (15), it is clear that CA XIV is the major membrane-associated CA in retina.…”
Section: Discussionmentioning
confidence: 99%
“…The deduced amino acid sequence includes an 18-residue signal sequence, a 260-residue segment exhibiting 30-36% sequence identity with other human carbonic anhydrase isozymes, and an additional 27-residue segment at the C terminus containing a 21-residue hydrophobic domain. The C-terminal domain likely specifies the association of CA IV with the membrane and contains a signal for posttranslational cleavage and transfer to the GPI anchor (18). Removal of the C-terminal domain results in a fully active, soluble, secretory form of CA IV with catalytic properties identical to those of GPI-anchored CA IV (19).…”
mentioning
confidence: 99%
“…The CA IV isozyme contains two disulfide linkages which contribute to its remarkable stability upon solubilization in 5% sodium dodecyl sulfate (SDS) (12,17). The full-length cDNA for human CA IV has been isolated from a gt10 kidney cDNA library and expressed in COS cells (18). The deduced amino acid sequence includes an 18-residue signal sequence, a 260-residue segment exhibiting 30-36% sequence identity with other human carbonic anhydrase isozymes, and an additional 27-residue segment at the C terminus containing a 21-residue hydrophobic domain.…”
mentioning
confidence: 99%
“…These results sug- gest that the CA II associated with apical plasma membranes of Capan-1 cells is bound to the inner leaflet. CA IV has been shown to be situated on the outer leaflet in many cell types, in line with the description of this enzyme as a GPI-anchored protein (Zhu and Sly 1990;Ghandour et al 1992;Okuyama et al 1992;Mairal et al 1996). On electron microscopic examination, the CA activity after the Hansson's reaction on both inner and outer leaflets of apical plasma membranes of Capan-1 cells was thought to indicate sites of activity of CA II and CA IV, respectively.…”
Section: Discussionmentioning
confidence: 73%